Intranasal administration of carbamazepine-loaded carboxymethyl chitosan nanoparticles for drug delivery to the brain - Shanshan Liu; Shili Yang; Paul C. Ho (Elsevier, 2018)
Epilepsy is considered as a common and diverse set of chronic neurological disorders and its symptoms can be controlled by antiepileptic drugs (AEDs). The presence of p-glycoprotein and multi-drug resistance transporters in the blood-brain barrier could prevent the entry of AEDs into the brain, causing drug resistant epilepsy. To overcome this problem, we propose using carboxymethyl chitosan nanoparticles as a carrier to deliver carbamazepine (CBZ) intra-nasally with the purpose to bypass the blood-brain barrier thus to enhance the brain drug concentration and the treatment efficacy. Results so far indicate that the developed CBZ-NPs have small particle size (218.76 ± 2.41 nm) with high drug loading (around 35%) and high entrapment efficiency (around 80%). The in vitro release profiles of CBZ from the NPs are in accordance with the Korsmeyer-peppas model. The in vivo results show that both encapsulation of CBZ in nanoparticles and the nasal route determined the enhancement of the drug bioavailability and brain targeting characteristics.